Digital Fundraising Innovation in an Islamic Philanthropic Institution: The Case of LAZ Yatim Mandiri - Lian Fuad (Cahaya Abadi Publisher, 2026)
The Islamic philanthropy sector in Indonesia is undergoing a significant transformation driven by rapid advancements in information technology. This study explores the innovation of digital fundraising at LAZ Yatim Mandiri within the context of digital transformation. Using a qualitative approach with a case study design, this research examines how the institution integrates technological innovation with conventional services to optimize the collection of Zakat, Infaq, Alms, and Waqf (ZISWAF). The results indicate that LAZ Yatim Mandiri implements a comprehensive hybrid strategy that combines a self-developed digital ecosystem, such as the Prima application and QRIS integration, with a physical presence of 46 service offices across 14 provinces. A key finding is the strategic application of the AISAS (Attention, Interest, Search, Action, Share) communication model, which effectively manages the donor journey from initial awareness to active participation. Digital platforms, including Instagram, TikTok, and the official website, are utilized not only for promotion but also as vital tools for transparency and community engagement through real-time reporting. This multidimensional approach demonstrates that digital fundraising is not merely a technical adjustment but a fundamental shift in organizational culture and governance. The study concludes that the success of digital innovation in zakat institutions depends on the ability to balance technological sophistication with local social relations and public accountability, thereby ensuring sustainable growth in a competitive philanthropic landscape.